Lideranças femininas em uma instituição financeira de natureza cooperativa: análise das condições que viabilizam as mulheres chegarem a cargos de liderança executiva - Gaspar, Karina da Silveira (Universidade do Vale do Rio dos Sinos, 2016)
This research has the main objective analyze the conditions that enable women, who make up the studied financial institution, to achieve the top leadership positions. The research was conducted by an exploratory qualitative research through interviews with 21 men and women in executive and middle leadership positions of a Brazilian credit union system, composed of 109 companies. After making the interviews, these are analyzed with the use of NVivo11 software, in addition, meetings were held with the professional responsible for the theme of diversity in the organization, and document analysis through reports of investigation were made. Research results have shown that attributes such as reliability, empowerment, people management, initiative and proactivity, performance, relationships, decision-making, are essential to women who want to get to high leadership positions, but they still need to overcome many barriers imposed both in society and also in the studied organization, because we still find situations of prejudice against women, in addition to a working structure environment does not favor the attraction and retention of women in senior management positions. The results also showed that due to a cooperative organization, its culture promotes the inclusion of women, since it brings in its essence the question of equality, but warns that the very scattered power also characteristic of this type of institution, which can often sometimes distort the basis of organizational culture, through the application of personal leader bias. It was observed that are development actions undertaken by the organization, but that these are offered equitably between men and women, however, due to the need to integrate female to top leadership positions, it is necessary to create actions more directed, which it is believed that this work will contribute. Finally, it was concluded that the future prospects for women who crave occupy executive leadership positions are very positive, as the organization demonstrates a clear desire to include women in strategic positions, however, it is necessary that women have more attitude, confidence, perseverance and appropriate professional qualifications.
Keywords: Liderança feminina; Diversidade de gênero em cooperativa; Gender diversity; Female lead; Gender diversity in cooperative; ACCNPQ::Ciências Sociais Aplicadas::Administração